Physicochemical Parameters and Their Toxicity Level for Recreational Activity and Plaque Psoriasis Healing Effects of Hot Spring Water of Kharapani, Pokhara, Nepal - Adhikari, Hari Sharan; Dhakal, Kedar Nath; Adhikari, Rameshwar (Journal of Engineering and Sciences, 2023)
The current study involved the determination of water quality parameters, inclusively the dissolved mineral levels, to assess the therapeutic and toxicity states of the hot spring water of Kharapani, Pokhara, Nepal. People have widely used the hot spring for taking baths and soaking in to heal from allergic and fungal ailments, musculoskeletal disorders, arthritis, and different diseases. The high values of alkalinity (700 ppm), total suspended solids with the size of at least 2 μm (TSS) (50 ppm), total dissolved solids (TDS) (650 ppm), turbidity (13 NTU), soluble carbonate (150 ppm), soluble chloride (250 ppm), surface tension (72.98 Dynes cm-1) and total hardness (880 ppm) showed the spring water was unsuitable for drinking, swimming and soaking in. The mineral levels at nitrate (undetectable), iron (II) (<0.3 ppm, undetectable), iron (II) (<0.3 ppm, undetectable), aluminum (III) (<0.3, undetectable) corresponded to safe utility levels, and the high sulphate content at 400 ppm showed that the spring was a sulphate rich hot spring with the properties of healing the fungal ailments and respiratory and musculoskeletal disorders. The hot spring water soakers reported healing and relief from itchy skin allergic rashes, and persisting skin disorders like acne, eczema, psoriasis, and joint pain, while the adverse effects such as skin blister, ooze and crust, dry and inflamed skin, dandruff, etc. were also found common among the prolonged soakers of the hot spring. The study showed an excellent healing effect of hot spring baths against psoriasis but associated with mild skin burn and dandruff. The study showed the necessity of technical moderation and maintenance of the minerals and water quality parameters at the acceptable range for swimming purposes.